TEACHING PRONUNCIATION THROUGH ENGLISH FILM AT A JUNIOR HIGH SCHOOL IN GARUT - Ade Wandi; Evie Kareviati (IKIP Siliwangi, 2023)
The aims of study is to determine the influence of watching English film towards students' pronunciation in speaking practice. The method was the quantitative method of pre experiment one group pretest posttest design. The population was taken from class VIII students from one of the junior high schools in Talegong in the 2020/2021 academic year. The data was taken from posttest and pretest one group design to know the students' pronunciation ability. The research was conducted by asking students to watch English film as a medium to improve students' pronunciation skills. The data that has been collected was analyzed using Paired T test and the results showed the pretest (0.007) and the post-test (0.16. It means that the results of pretest was lower than posttest. To find out the difference in these values, then the researcher used a paired Sample T test to organize the parametric statistical data of the study so that they are normally distributed. The data showed that the Sample Paired T test sig (two sides) is 0.000, with a significance level of 0.05. The result is a significance of 0.000 and < 0.05 meaning that the results are lower than the significant level, there is a difference between the post test and pretest data. We can conclude that the hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. It shows that the students’ pronunciation is improved through watching English film many times.